Pre-hatching exposure to water mold reduces size at metamorphosis in the moor frog. - Uller, T; Sagvik, J; Olsson, M (2009)
Developmental plasticity is increasingly recognized as important for ecological and evolutionary processes. However, few studies consider the potential for delayed effects of early environments. Here, we show that tadpoles hatching from clutches exposed to water mold (Saprolegnia) have 20% decreased mass at metamorphosis, despite no further exposure subsequent to hatching. The effects were consistent across four populations that have previously been shown to vary in their resistance to infection during embryonic development. Contrary to expectations, time to hatching or metamorphosis was not affected, suggesting that the results do not reflect an evolved escape strategy from infected waters triggered by embryonic conditions. Instead, decreased mass at metamorphosis may arise from carry-over effects of impaired embryo development. Such strong links across developmental stages have potential consequences for the evolution of plasticity and the responses of populations to emergent infections.